Buku Biografi Visual Grup Kasidah Modern Nasida Ria - Masnuna; Danar Rizkiardi; Aditya Rahman Yani (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2021)
Nasida Ria, a modern kasidah music group, is known as a kasidah legend in Indonesia. Formed in an area with a background that is identical to Islamic values, namely the Kauman area, Semarang, Central Java in 1975 by H. Muhammad Zain, they have a main mission of preaching but in a way that many people like, namely music. In her 45 years of career, Nasida Ria has produced hundreds of works that can be enjoyed by the public. They have proven to the public that with its uniqueness and distinction, Nasida Ria is able to fight the times amidst the dynamics of the Indonesian music industry, as well as the twists and turns of her career so that she is able to become a kasidah legend in Indonesia. Their extraordinary career journey has inspired the formation of this visual biography. The illustration that summarizes the story of Nasida Ria's career is the strength of the attraction of this biography. With the visual biography of the modern Kasidah group Nasida Ria, the information that the audience needs to convey or need is well-structured and interesting.